The effect of paint types toward iris color changes of ocular prosthetics - Sarjono, Gunawan Sri; Ismiyati, Titik; Wahyuningtyas, Endang (Faculty of Dentistry, Universitas Gadjah Mada, 2020)
Ocular prosthetics are mainly created to meet the aspect of esthetic consideration. The paint application in ocular prosthetics construction is remaining an option for Prosthodontist. This study aims to examine the effect of types of paint toward iris color change of the ocular prosthetics. Three black types of paint: oil paint (Maries Oil Color, China), automotive paint (Avian, Indonesia), and acrylic paint (Sakura, Japan) were used to paint paper disc to produce 27 iris ocular prosthetics. Chromameter was used to examine the first and the final color after acrylic processing using themicrowave. The measurement results in the process using Commission Internationale de l’Eclairage. One-way ANOVA test showed significant differences between the three types of paints on ocular prosthetics (p<0.05). The LSD test revealed that oil paint groups had more significant results than the automotive paint group and acrylic paint group, while the automotive paint group did not have significant differences with the acrylic paint group (p>0.05). Thus, it is conclusive that oil paint influences the iris color change of the ocular prosthetics.